Pengaruh Kepercayaan, Kemudahan, dan Keamanan terhadap Keputusan Pembelian di Marketplace - Agustiningrum, Dian; Andjarwati, Anik Lestari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine the effect of trust, comfort, and security on purchasing decisions at Shopee. With the development of an online shopping system that uses the internet, people are now following developments by having a mindset of consumer behaviour from conventional shopping to shopping digitally and online. Consumer confidence in online shopping through the system is very concerned about avoiding things that are not desirable. Therefore, it is necessary to ease of use of the system and strict security to conduct transactions online. The sample in this study were 200 respondents who were Shopee application users, both men and women aged 19-27 years. This study uses multiple linear regression analysis techniques through the analysis tool IBM SPSS statistic version 26. This study indicates that the variables of trust, security, and convenience affect purchasing decisions. The Shopee application is expected to further improve the quality of service through what consumers feel through reviews about the Shopee application in terms of the trust, convenience, and security or other things if it is deemed unsatisfactory. This study recommends marketers to maintain customer loyalty. The Shopee application must also maintain the ease of use of the application, such as the development of the latest features that are more attractive and practical to make it easier for consumers to search for products until they decide to make transactions.